Peran Pemerintah Indonesia dalam Menyikapi Pola Perilaku Herd Investor di Pasar Obligasi Pemerintah pada 5 Negara ASEAN - Mugiharto, Rahmanul Yusuf; Soesilo, Nining I (Jurnal Kebijakan Ekonomi, 2023)
This study aims to determine the pattern of investor behavior using the Cross Sectional Absolute Deviation (CSAD) method with daily data yield of 10Year SUN for the period January 2007 to October 2020 and 10Year Sukuk for the period January 2013 – October 2020. The study shows that herd investors for SUN instruments are influenced by yields on the EMA associated with the economic crisis and yields on UST are associated with SUN ratings. Another factor is the use of appreciation and criticism variables that have an impact on the yield of SUN and Sukuk. The two instruments are complementary instruments in the SBN market, so the role of the Indonesian government is very important to address the behaviour patterns of herd investors in the government bond market.